Brazil - Public Expenditures for Poverty Alleviation in Northeast Brazil : Promoting Growth and Improving Services - World Bank (Washington, DC, 2013)
This report addresses the role public expenditure can play in the alleviation of poverty in the Brazilian northeast, involving both regional growth, and social services. Notwithstanding relatively high growth in the past two years, the northeast lags behind the rest of the country, with a per capita GDP just under sixty percent of the country's GDP, with no significant variations since 1965. Based on national statistical data, the study identifies private investment as a principal determinant of regional growth, and, although public investments do not appear to effect growth directly, it does indirectly in so far private investment can be stimulated. The analysis further indicates that certain type of infrastructure investments, that lower local cost of production in the region (i.e., electric power, and water supply) are associated with increased private investment. However, public infrastructure investments (i.e., transportation, and communication) that increase regional integration with the rest of the country, have mixed effects. Results largely confirm that public investment should be complementary to private investment, by providing goods, or overcoming other market failures, rather than substituting for private activities. And also, results point to a possible interregional externality, i.e., that the returns to state investments in education may well accrue to other states. It is suggested that infrastructure supporting the creation of off-farm employment is necessary, that guiding urban development is a high priority, while in the short-run, agriculture will remain a prominent feature of the northeast economy.